2013
DOI: 10.4049/jimmunol.1202104
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant Anti-Insulin B Cells Are Effective APCs

Abstract: Autoreactive B lymphocytes that are not culled by central tolerance in the bone marrow frequently enter the peripheral repertoire in a state of functional impairment, termed anergy. These cells are recognized as a liability for autoimmunity, but their contribution to disease is not well-understood. Insulin-specific 125Tg B cells support T cell-mediated Type 1 diabetes (T1D) in nonobese diabetic (NOD) mice, despite being anergic to B cell mitogens and T cell dependent immunization. Using this model, the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 42 publications
8
55
2
Order By: Relevance
“…Ag internalization was performed as previously described (8). Briefly, freshly isolated bone marrow and spleen cells were incubated with biotinylated insulin for 30 min on ice to occupy BCR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ag internalization was performed as previously described (8). Briefly, freshly isolated bone marrow and spleen cells were incubated with biotinylated insulin for 30 min on ice to occupy BCR.…”
Section: Methodsmentioning
confidence: 99%
“…B cells expressing transgenic BCR specific for insulin (125Tg) have an anergic phenotype, characterized by lack of calcium signaling upon engagement with their Ag, loss of proliferative response to B cell mitogens, and failure to produce Ab in response to T-dependent immunization (5, 6). Nevertheless, these tolerant B cells can present Ag to T cells and promote development of type 1 diabetes (T1D) in the NOD mouse background (7, 8). In this model, the BCR affinity for insulin is moderate ( K d = 10 −7 M) (9); the small, soluble Ag does not strongly cross-link the BCR; and the cells develop normally to fill all mature splenic subset niches (6), allowing study of a population that may mimic tolerant autoreactive cells in a natural repertoire.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TLR-4 stimulation by LPS unlocks alternate signaling pathways to ERK phosphorylation and NF-κB activation independent of conventional BCR-dependent signaling mediators (20) that may be impaired for anergic B cells. Adaptive interactions with T cells may also drive loss of B cell tolerance and promote somatic hypermutation and Ig class switch recombination (CSR) in germinal center (GC) reactions associated with ongoing autoimmune disorders (21, 22). The fact most pathogenic autoAbs are of the IgG isotype further implicates T cells as potential vectors for driving loss of B cell tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using a conventional IgM-restricted anti-insulin BCR transgene revealed that anti-insulin B cells enter the mature repertoire but are anergic and fail to produce anti-insulin Abs following T cell-dependent (TD) immunization (25). Such functionally silenced B cells residing in the periphery retain cellular functions such as Ag presentation that enable them to promote autoimmunity in NOD mice (22, 26). Insulin autoAbs associated with autoimmune disorders like type 1 diabetes, as well as Abs that arise in response to insulin therapy and complicate disease management, are predominantly of the IgG isotype (2732).…”
Section: Introductionmentioning
confidence: 99%